THE STUDY OF HOSPITALIZATION CASES IN OSTEOCHONDROSIS OF THE SPINE: KEY ASPECTS AND CHARACTERISTICS OF THE DISEASE - Bakhromjon M. Mamatqulov; Dilorom A. Umurzakova (Central Asian Journal of Medicine, 2024)
The article is devoted to the peculiarities of the incidence of osteochondrosis of the spine among hospitalized patients. In the course of the study, an analysis of clinical cases of patients diagnosed with osteochondrosis was carried out, which made it possible to identify the characteristic features of hospitalized morbidity and characteristics of this disease. The analysis of statistical data helped to identify the types and frequency of hospitalizations, the types of medical services received, as well as differences among different gender and age groups. Information on the prevalence of the disease among men and women, as well as its impact on different age cohorts and professions, will be an important addition to the general understanding of the problem. The presented statistical data help to assess the prevalence of the disease and its impact on the population. The results obtained contribute to a deeper understanding of the problem and the development of targeted measures to prevent it.